Multifunctional and Redundant Roles of Borrelia burgdorferi Outer Surface Proteins in Tissue Adhesion, Colonization, and Complement Evasion - Caine, Jennifer A.; Coburn, Jenifer (Frontiers in Immunology, 2016)
Borrelia burgdorferi is the causative agent of Lyme disease in the U.S., with at least 25,000 cases reported to the CDC each year. B. burgdorferi is thought to enter and exit the bloodstream to achieve rapid dissemination to distal tissue sites during infection. Travel through the bloodstream requires evasion of immune surveillance and pathogen clearance in the host, a process at which B. burgdorferi is adept. B. burgdorferi encodes greater than 19 adhesive outer surface proteins many of which have been found to bind to host cells or components of the extracellular matrix. Several others bind to host complement regulatory factors, in vitro. Production of many of these adhesive proteins is tightly regulated by environmental cues, and some have been shown to aid in vascular interactions and tissue colonization, as well as survival in the blood, in vivo. Recent work has described multifaceted and redundant roles of B. burgdorferi outer surface proteins in complement component interactions and tissue targeted adhesion and colonization, distinct from their previously identified in vitro binding capabilities. Recent insights into the multifunctional roles of previously well-characterized outer surface proteins such as BBK32, DbpA, CspA, and OspC have changed the way we think about the surface proteome of these organisms during the tick–mammal life cycle. With the combination of new and old in vivo models and in vitro techniques, the field has identified distinct ligand binding domains on BBK32 and DbpA that afford tissue colonization or blood survival to B. burgdorferi. In this review, we describe the multifunctional and redundant roles of many adhesive outer surface proteins of B. burgdorferi in tissue adhesion, colonization, and bloodstream survival that, together, promote the survival of Borrelia spp. throughout maintenance in their multi-host lifestyle.